Sosialisasi Anti-Bullying Berbasis Empati dalam Membangun Sikap Saling Menghargai pada Siswa Sekolah Dasar di Desa Kemiri Kab. Tangerang - Nur Azmi Wiantina; Febri Dahlia; Haura Fidiyah Asy Syahidah; Nabila Yunita Sari; Pahrudin Pahrudin; Ni Kadek Dwi Ningsih Rabuana (Education and Community Service Journal (EduServe), 2026)
Bullying in elementary school environments remains a significant issue that can hinder students’ character development, mental health, and social interactions. Initial observations and interviews with school representatives revealed that many students at SDN 01 Kemiri and SDN 02 Kemiri had not yet fully understood the various forms of bullying and their impacts on victims and the school environment. Therefore, this community service program aimed to enhance students’ understanding and awareness of bullying prevention through an empathy-based educational approach. The program was implemented at SDN 01 Kemiri and SDN 02 Kemiri through several stages, including problem identification, coordination with school authorities, preparation of educational materials, interactive socialization sessions, group discussions, question-and-answer activities, and program evaluation. The materials covered the definition of bullying, its various forms, the consequences of bullying, and strategies for prevention and reporting bullying incidents. The results indicated that students developed a better understanding of bullying behavior, were able to identify common forms of bullying occurring in the school environment, and demonstrated increased awareness of the importance of mutual respect in creating a safe learning atmosphere. Furthermore, the program fostered a shared commitment among students and school stakeholders to support the development of a child-friendly and bullying-free school culture. This empathy-based anti-bullying socialization program can serve as an effective preventive strategy for strengthening character education in elementary schools.